Autonomous learning and self-esteem In university students of Moquegua, 2023 - Rodríguez Benavides, Madyer Vanny (2024)
The proposal is to prove that a positive link is generated between personal appreciation and autonomy in learning by university students from Moquegua 2023. For them, there were 175 students who are in the last cycles of the universities in the region. It is a basic study, with an experiential, cross-sectional design, applied Rho statistical tests. Among the results, Spearman's correlation between "personal appreciation" and "Autonomous learning" r=0.576, which indicates a moderate correspondence. Between "Self-perception" and "Autonomous learning" r=0.529, moderate positive correlation. Between "Social Relations" and "Autonomous Learning" r=0.515. This suggests that people who report better social relationships also tend to have a higher level of autonomous learning. Between autonomy, competence and autonomous learning, r=0.493. Conclusion. This suggests that as individuals perceive themselves as more autonomous and competent, they are more likely to develop autonomous learning skills. There is a link between personal appreciation and autonomous learning. That young people can develop better self-regulated learning when they better appreciate themselves.